The recovery and maintenance of the truth - Gardiner, Alfred John (Kingston-on-Thames, UK Stow Hill Bible and Tract Depot)
Includes numerous letters between brethren.
Brethren writer. Foreword dated 1951.
Keywords: Brethren movement -- doctrine and practice -- divisions